URGENSI PENAMBAHAN MASA JABATAN PIMPINAN KOMISI PEMBERANTASAN KORUPSI PRESPEKTIF HUKUM TATA NEGARA - Risma Juliana; Abdul Razak; Eza Tri Yandy (Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research aims to find out what is behind the increase in the term of office of the leadership of the Corruption Eradication Commission in Indonesia. Also, the urgency of increasing the KPK's term of office is viewed from the perspective of constitutional law. This research is normative legal research that uses a case approach with data collection methods through literature study. Based on the research, the results and conclusions obtained are related to the Constitutional Court decision Number 112/PUU-XX/2022 regarding the term of office of the KPK leadership proposed by Nurul Ghufron as deputy chairman of the KPK for the 2019-2023 period. The reason for the request is related to the applicant's age when he was appointed, 45 years old, and when his position ended, he was 49 years old. So he cannot nominate himself as KPK leader for the next period as stated in Article 29 letter (e) of Law Number 19 of 2019. Also, the term of office for KPK leaders is 4 years for re-election for one period in Article 34 of Law No. 30 of 2002 is considered discriminatory regarding the terms of office of heads of other independent state institutions. The applicant feels that his constitutional rights have been violated due to injustice, discrimination and legal uncertainty. This decision is considered not urgent and is not in accordance with the concept of constitutional theory, justice and legal certainty. The age restriction setting is an open legal policy. And increasing the term of office of the KPK is not urgent considering the performance and achievements of the current KPK leadership. Keywords: Urgency of Term of Office, Corruption Eradication Commission, Constitutional Law